PERANCANGAN PROTOTYPE TEKNOLOGI SMART BUILDING MENGGUNAKAN ARDUINO BERBASIS WEB SERVER UNTUK MENDUKUNG PEMBANGUNAN PROPINSI LAMPUNG MENUJU PROGRAM LAMPUNG SMART CITY - Budi Usmanto; Tri Susilowati (IIB Darmajaya, 2017)
Smart Building System is an application system that is a combination of technology and services devoted to the home or building environment with specific functions aimed at improving the efficiency, comfort and security penghuninya.Berdasarkan it in this study designed and made prototype automation system on building arduino web server. This system serves to monitor temperature, humidity, voltage detection and electrical current, fire detection, rain intensity detection, smoke detection, earthquake detection, flood detection, and movement detection if there are people who infiltrated the house or building. It also integrates with the electrical devices used to monitor and control the lights associated with a relay, and to move the servo that serves as a fence-opening and closing device. The Arduino Web Server is comprised of a combination of arduino uno and Ethernet shield, acting as an embedded web server that acts as both an overall monitoring and controller of the system. The system as a whole can be accessed anytime and anywhere through computers and smartphones in realtime using the browser. This system will also provide the latest information in realtime in case of unwanted things through Twitter and Facebook. Keywords: smart building, smart city, web server, arduino